IDENTIFICATION OF SITE SPECIFIC EUCALYPTUS CAMALDULENSIS CLONES FOR TIRUPATHI (ANDHRA PRADESH) BASED ON ITS PRODUCTIVITY - Arumugam, Vijayaraghavan; Veerasamy, Sivakumar; R.Yasodha,; R.Anandalakshmi,; Smitha G Nair,; A.Anees,; G.Suresh, (IJRDO-Journal of Applied Science, 2020)
Eucalyptus camaldulensis and Eucalyptus tereticornis clones were shortlisted based on individual tree superiority observed in the multilocational clonal trial for growth attributes like height, girth at breast height and volume. Clonal trials were planted with commercial clones, seedlings from seed orchard, IFGTB and local seedlings during the year 2009-10 to identify the best performing and site specific clones. The clones were planted at the experimental site of Andhra Pradesh Forest Department (KFD) at Tirupathi. The growth parameters like height, girth at breast height and its volume were recorded at its half rotation (2010 to 2014). Ranking of the 22 commonly planted clones and two seed lots showed that Clone C-10 and C-19 were consistently superior in their growth performance when compared to all other clones, seed lot and the commercial clones with respect to height, girth and volume although the performance changed with each characters. Based on the study it was concluded that the clones viz., C-10 and C-19 are best suitable for the area in and around Tirupathi and also for having the same soil characteristics (sandy clay loam). The results confirm that the clones selected and tested in test environments will perform similarly in similar site conditions if deployed.